2018
DOI: 10.1186/s13075-018-1692-y
|View full text |Cite
|
Sign up to set email alerts
|

An explorative study on deep profiling of peripheral leukocytes to identify predictors for responsiveness to anti-tumour necrosis factor alpha therapies in ankylosing spondylitis: natural killer cells in focus

Abstract: BackgroundTherapeutic targeting of tumour necrosis factor (TNF)-α is highly effective in ankylosing spondylitis (AS) patients. However, since one-third of anti-TNF-treated AS patients do not show an adequate clinical response there is an urgent need for new biomarkers that would aid clinicians in their decision-making to select appropriate therapeutic options. Thus, the aim of this explorative study was to identify cell-based biomarkers in peripheral blood that could be used for a pre-treatment stratification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…In addition, HLA-E expression was also increased in CD14 + monocytes of these patients, suggesting that this signaling pathway was functional in AS ( 298 ). A recent study demonstrated that increased number of CD8 expressing NK cells was associated with a better clinical response to anti-TNF-α therapies and could be suggested as a biomarker for monitorization of a better treatment response ( 299 ).…”
Section: Natural Killer Maturation Phenotypes Distribution and Funcmentioning
confidence: 99%
“…In addition, HLA-E expression was also increased in CD14 + monocytes of these patients, suggesting that this signaling pathway was functional in AS ( 298 ). A recent study demonstrated that increased number of CD8 expressing NK cells was associated with a better clinical response to anti-TNF-α therapies and could be suggested as a biomarker for monitorization of a better treatment response ( 299 ).…”
Section: Natural Killer Maturation Phenotypes Distribution and Funcmentioning
confidence: 99%
“…A high-dimensional, multi-parametric flow cytometric analysis was applied to identify cell surface biomarkers as potential immunophenotypic predictors of response to anti-TNF agents in 31 patients with axSpA ( 41 ). Low frequency of a subpopulation of NK cells expressing CD8 was associated with a lack of response (AUC 0.79).…”
Section: Theragnostic Biomarkersmentioning
confidence: 99%
“…Therefore, exploring factors that influence immune cell number and function will play a critical role in understanding the pathogenesis of these diseases and identifying new treatment strategies. TNF-α inhibitor has been shown to have an anti-inflammatory effect in treating AS [12], but its potential beneficial effects on the bone structure are still challenging to identify and its mechanisms remain unclear. Although targeting of TNF-α is very effective in AS, around one third of treated patients show only a poor response.…”
Section: Introductionmentioning
confidence: 99%